Maternal Risk Factors and Outcomes of Low Birth Weight (Journal of Rangpur Medical College, 2025)
Background: Low birth weight babies carry a relatively higher risk of perinatal and neonatal mortality and retarded growth and development subsequently. Objective: The general objective of this study was to find out the maternal risk factors & outcome (morbidity and mortality) of LBW babies. Methods: This case-control study was carried out in the Department of Obstetrics and Department of Pediatrics at Sir Salimullah Medical College and Mitford Hospital, Dhaka, from Febuary 2014 to July 2014. Among 50 newborns,75 cases (newborns with low birth weight, LBW) and 75 controls (healthy newborns). Statistical analysis was carried out by using the statistical package for social sciences (SPSS) for Windows version 22. The differences between groups were analyzed by unpaired t-test or chi-square test and also the odd ratio was used for testing risk factors associated with low birth weight. A p-value < 0.05 was considered as significant. Results: Important maternal risk factors were primi parity(40% in cases Vs 27% in control), age < 20 years (53% Vs 27%), hypertension (26% Vs 9%), preeclampsia (14% Vs 4%), prolonged rupture of membrane (14% Vs 9%), APH (20% Vs 14%), multiple births (7% Vs 4%), anemia (9% Vs 7%). All these were statistically significant (p